The Influence of Word of Mouth, Product Completeness and Product Attractiveness on Fertilizer Purchase Decisions at Growmart (Cab. Usaha Tani) - Sinaga, Hommy Dorthy Ellyany; Setyorini, Dian; Januari, Amanda Putri (Dinasti Publisher, 2025)
This study aims to analyze the influence of word of mouth, product completeness, and product appeal on fertilizer purchasing decisions at Growmart (Agricultural Business Branch) located on Jl. Jenderal Sudirman, Bagan Batu, South Labuhanbatu, Riau. The background of this study is based on the tight business competition in the agricultural sector and the low volume of fertilizer sales at Growmart, which is suspected to be influenced by the less than optimal marketing strategy and the mismatch of stock with consumer needs. This study uses a quantitative approach with a survey method through a questionnaire distributed to 292 respondents, determined by the Slovin formula from a population of 1,076 people. The sampling technique uses the random sampling method. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (Adjusted R²). The results of the study showed that partially and simultaneously, the variables word of mouth, product completeness, and product appeal have a significant effect on fertilizer purchasing decisions at Growmart. Word of mouth has a positive influence because it provides information that is trusted by consumers. Completeness of the product encourages consumers to buy in one place practically. While the appeal of the product increases interest through attractive visuals, packaging, and presentation